Методика визначення параметрів контактного теплового акумулятора фазового переходу двигуна у складі комплексної системи комбінованого прогріву - Грицук, Ігор Валерійович (НТУ "ХПІ", 2015)
У статті описана методика визначення параметрів контактного теплового акумулятора з фазовим переходом у складі комплексної системи комбінованого прогріву для зберігання теплової енергії двигуна транспортного засобу або енергетичної установки в міжзмінний період. Методика дозволяє повною мірою урахувати умови експлуатації і включає в себе всі процеси роботи контактного теплового акумулятора комплексної системи комбінованого прогріву.

The article describes the method of determining the parameters of the thermal contact with the battery phase transition in the complex system of combined storage heating heat engine or vehicle power plant in the period between variables. The results are a useful basis for the design of heating motors with thermal battery contact phase transition and adjustment of parameters in the experimental studies and optimization of structural elements. The ultimate goal of the calculation and estimation of parameters of contact thermal power in the complex system of combined heating engine - determination of variable values of parameters that yield the extreme value parameter optimized. It was selected parameter optimization, which is the objective function of a number of variables, calculated by finding its extremum using modern computer technology and programs. The technique allows to fully take into account the operating conditions and includes all processes of contact thermal power complex system of combined heating. The study using thermal contact with the battery phase transition confirmed that, in general, its use in complex systems combined heating advisable for long-term storage of heat engine vehicle and power installation with no engine running in different climatic conditions and configuration features and the use of technology chosen depending on the operational needs and purpose of the engine.
Method of calculating contact heat storage phase transition of the engine in the complex system of the combined warming
Keywords: транспортний засіб; енергетична установка; експлуатація; зберігання теплової енергії; vehicle; power installation; operation; storage of heat; contact heat storage; phase transition; complex system of combined heating